Inverse correlation between salt tolerance and host-adaptation in mycobacteria. (December 2016) - Asmar, Shady; Sassi, Mohamed; Phelippeau, Michael; Drancourt, Michel
Abstract Background The genusMycobacterium includes host-adapted organisms regarded as obligate and opportunistic pathogens and environmental organisms. Factors contributing to this wide range of adaptations are poorly known. Results We studied the salt tolerance of 46Mycobacterium species of medical interest. Representative strains of theMycobacterium tuberculosis complex, Mycobacterium avium complex, Mycobacterium chelonae -abscessus complex, Mycobacterium ulcerans, Mycobacterium marinum, Mycobacterium lentiflavum, Mycobacterium fortuitum andMycobacterium conceptionense were inoculated on Middlebrook 7H10 medium supplemented with 0–10 % sodium chloride. Colonies were counted after 2–4 week incubation at the appropriate 30–37 °C temperature depending on the tested strain. Further comparative genomics was done on 15Mycobacterium strains representing the spectrum of salt-tolerance of mycobacteria. Based on the results the different species were grouped according to their salt tolerance into a "salt-sensitive" group (growth up to ≤3 % salt) containing theM. tuberculosis complex, Mycobacterium chelonae, Mycobacterium lentiflavum, Mycobacterium ulcerans andMycobacterium marinum ; a "salt-intermediate" group (growth between 4 and 6 % salt) comprisingMycobacterium avium, Mycobacterium intracellulare, Mycobacterium chimaera and a "salt-resistant" group (growth up to >6 %) comprisingMycobacterium homonissuis, Mycobacterium bolettii, Mycobacterium fortuitum andMycobacterium conceptionense . Genomic analysis revealed that 290 genes were unique to species belonging to the salt-sensitive group; and that 15 % were annotated as being functionally associated with the ESX secretion systems Pro-Glu and Pro–Pro-Glu family proteins. Conclusions In this work we found an inverse correlation between salt tolerance and host adaptation. We thus propose that salinity is one of the multiple factors determining the ecological niches of mycobacteria.